Systems Strengthening for Resilience: Climate Risk Management in Agricultural Extension in Ethiopia and Beyond - Grossi, Amanda; Dinku, Tufa; Hansen, James; Trzaska, Sylwia; Teshome, Fetene; Teshome, Asaminew; Lemma, Esayas; Gebre, Andualem; Alemayhu, Fekadu; Bulo, Milion; Ahmed, Jemal Seid; Gebrehawariat, Girma; et al. (Accelerating Impacts of CGIAR Climate Research for Africa, 2024)
The collaborative development of Climate Risk Management in Agricultural Extension (CRMAE) curriculum is the first of its kind, building foundational knowledge and skills for extension workers to help farmers better plan for, manage, and respond to climate risk. The curriculum bundles training on freely available and tailored climate information service innovations and approaches to advance climate-smart agriculture at local scales. Following Ethiopia’s example, South-South learning and sharing has spurred the co-development of the curriculum in all six focus countries of the AICCRA project, amongst 70 institutions representing a swathe of public and private extension and advisory service providers. E-learning presents unique opportunities to scale access and use of the curriculum.